FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEPATUHAN MASYARAKAT TERHADAP PROTOKOL KESEHATAN COVID-19 - Felix Kasim; Beni Satria; Balqis Wasliati; Kuat Sitepu; Ika Nur Saputri; Henri GudmenRionald Sihite (JURNAL KESMAS DAN GIZI (JKG), 2021)
The COVID-19 pandemic outbreak is increasingly deadly and is expanding beyond China. Batu Bara Regency is one of the districts that has experienced an increase in confirmed cases of COVID-19. The success of the COVID-19 health protocol practice is largely determined by the compliance of the community in carrying out the 3M movement, namely using masks, washing hands with soap, and maintaining physical distance. The purpose of this study was to determine the factors related to community compliance with the COVID-19 health protocol in Datuk Lima Puluh District, Batu Bara Regency. This study was an observational analytic study with a cross sectional design. The population in this study were all people in Datuk Lima Puluh District, Batu Bara Regency and the total sample was 393 people. Data collection was carried out with primary and secondary data. Data analysis was performed using the chi-square test and multiple logistic regression. The results of the chi-square test show that there is a relationship between knowledge and availability of facilities and community compliance with the COVID-19 health protocol in Datuk Lima Puluh District, Batu Bara Regency. The results of multiple logistic regression tests show that respondents who do not have the availability of facilities have 1,904 times the chance of not adhering to the COVID-19 health protocol. Suggestions for the health office and health services are expected to increase health socialization related to the prevention of COVID-19 so that people can comply with health protocols.